Potensi Tanaman Obat Indonesia sebagai Kandidat Terapi Pendukung pada Demam Berdarah Dengue - Terza Aflika Happy; Linda Septiani; Risti Graharti; Femmy Andrifianie (Medula, 2026)
Dengue Hemorrhagic Fever (DHF) remains a major public health problem in Indonesia, with high morbidity and mortality rates. Since the current management of DHF is primarily supportive, identifying effective complementary therapies has become an important research priority. Indonesia possesses extraordinary biodiversity, including numerous medicinal plants rich in bioactive secondary metabolites with potential therapeutic properties. This study aimed to review the potential of Indonesian medicinal plants as candidates for supportive therapy in DHF based on available scientific evidence. A literature review was conducted by analyzing national and international publications related to medicinal plants and dengue infection. The findings indicate that several Indonesian medicinal plants, including Phyllanthus niruri L., Psidium guajava, Carica papaya L., and Ipomoea batatas, demonstrate promising potential as supportive therapies for DHF. Their therapeutic effects are mainly attributed to bioactive compounds such as flavonoids, quercetin, saponins, tannins, alkaloids, and polyphenols, which exhibit antiviral, anti-inflammatory, antioxidant, and immunomodulatory activities. These compounds may also promote thrombopoiesis by stimulating granulocyte-macrophage colony-stimulating factor (GM-CSF) and interleukin-3, thereby contributing to platelet recovery. In addition, they help reduce oxidative stress, suppress excessive pro-inflammatory cytokine production, and preserve vascular endothelial integrity, potentially preventing disease progression and plasma leakage. Overall, Indonesian medicinal plants represent promising candidates for complementary supportive therapy in DHF. Nevertheless, further preclinical investigations and well-designed clinical trials are required to confirm their efficacy, safety, optimal dosage, and mechanisms of action before they can be recommended for routine clinical practice.